Multidimensional Meanings and Ritual Practice of Phra That Nakhon Through the Literary Realm of Legends and Chronicle of Phra That Nakhon Si Thammarat - Seubsakulajinda, Vanpra; Khemakhunasai, Pornphan; Sirisatidkit, Pornthai (Journal of Thai Studies, 2024)
Background and objective (s) : Most of the studies of Phra That Nakhon (Phra That Nakhon Si Thammarat Relics Pagoda) present that the pagoda symbolizes the Buddhist and political centrality of the Thai peninsula in the traditional period, as well as that PhraThat Nakhon itself represents the provincial identity of Nakhon Si Thammarat. These suggestions lead to the researcher’s observation that the pagoda’s religious and political meanings, along with the sense of identity representation, have possibly been created through literature that mentions the establishment of Phra That Nakhon – the narratives that have been widely reproduced later because many versions significantly differ in details. The research for this article, thus, aimed to analyse the construction of multidimensional meanings towards Phra That Nakhon, as well examine the dynamism and diverse interpretations, through the legends of Phra That Nakhon and the chronicle of Nakhon Si Thammarat. Methodology: As documentary research, 13 versions of ancient documents that mention the establishment of Phra That Nakhon were selected and critically analysed using a conceptual framework of construction practices, dynamism and the contestation of meanings. Main result: Phra That Nakhon was initially established by provincial rulers as a political centre, so the related literature emphasized the sense of their political power towards the establishment of the principal state and its dominated towns, the administration of both territorial areas and citizens, and power relations. Later, Phra That Nakhon was regarded by regional Buddhists as a religious centre, and thus the Buddhist narratives emphasizing the people’s faith were created. Therefore in the early period, the establishment of Phra That Nakhon was utilized by the rulers to construct their political power through the pagoda’s spirit-worshipping ceremony and the reproduction of the chronicle to be kept in the principal state building. Afterwards, Buddhists with great faith tried to reinterpret the meaning of the pagoda – to identify Phra That Nakhon as a religious centre through the reproduction of oral literature named Phra Nipphat Sot (The time of the death of the Buddha (Parinivarna)), along with the creation of a related ritual practice called Suat Dan (the rhythmical recitation of Phra Nipphat Sot along the galleries of Phra That Nakhon). This interpretation has become widespread amongst Buddhists since the 20th CE. Relevance to Thai Studies: This descriptive research that critically analyses local literature, the legends and chronicle of Nakhon Si Thammarat is beneficial to a comparative study of local Thai literature. Conclusion: This study indicates that each version of literature related to the establishment of Phra That Nakhon differs from others in certain details such that multidimensional meanings of the pagoda have been significantly constructed and brought about the contestation of meanings depending on a particular group’s interpretation.